THE EFFECT OF BREASTFEEDING BOOSTER FOR BREASTFEEDING MOTHERS IN PEKALONGAN REGENCY - Lia Dwi Prafitri; Nina Zuhana; Wahyu Ersila (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
Exclusive breastfeeding is given since the baby is born until the age of two years. Increasing Human Resources by increasing the understanding and knowledge of mothers in giving breast milk was needed to support breastfeeding. Education on breastfeeding booster was expected to help mothers successfully breastfeed. The purpose of this study was to determine the effect of the breastfeeding booster package for breastfeeding mothers in Pekalongan Regency. This research used a Quasi Experiment research design with One Group Pretest and Posttest Design. The population in this study were all breastfeeding mothers in Pekalongan Regency in 2018. This study was conducted in September 2018 to August 2019, with non-probability sampling techniques using cluster sampling with a sample size of 79 respondents. Data analysis in this research was the Wilcoxon test. The results showed a p-value of 0.000 (0.05); this means that there is an effect of the breastfeeding booster package for nursing mothers. Public Health Centre was expected to be able to support and facilitate health workers, especially midwives, in providing information to breastfeeding mothers about the importance of breastfeeding booster packages to improve the quality and quantity of breast milk. Keywords: breastfeeding booster, Breastfeeding Mothers